2014
DOI: 10.1007/s00442-014-2964-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phylogeny, leaf traits, and the altitudinal distribution of host plants on herbivore assemblages on congeneric Acer species

Abstract: Historical, niche-based, and stochastic processes have been proposed as the mechanisms that drive community assembly. In plant-herbivore systems, these processes can correspond to phylogeny, leaf traits, and the distribution of host plants, respectively. Although patterns of herbivore assemblages among plant species have been repeatedly examined, the effects of these factors among co-occurring congeneric host plant species have rarely been studied. Our aim was to reveal the process of community assembly for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…We transformed data of leaf traits to homogenize variances and linearize relationships between variables. Th e scores of each principal component represent particular combinations of diff erent resistance traits and can be used as a proxy of a defensive index ( Barber and Marquis, 2011 ;Pearse and Hipp, 2012 ;Nakadai et al, 2014 ).…”
Section: Study Site -Fieldwork Was Done At the Centro De Investigacionesmentioning
confidence: 99%
“…We transformed data of leaf traits to homogenize variances and linearize relationships between variables. Th e scores of each principal component represent particular combinations of diff erent resistance traits and can be used as a proxy of a defensive index ( Barber and Marquis, 2011 ;Pearse and Hipp, 2012 ;Nakadai et al, 2014 ).…”
Section: Study Site -Fieldwork Was Done At the Centro De Investigacionesmentioning
confidence: 99%
“…Twenty‐eight Acer species occur in Japan (Nakadai et al . ), and a previous study confirmed 14 Acer ‐feeding Caloptilia species; 13 of the 14 Caloptilia species formed a monophyletic group, together with a Toxicodendron ‐feeding Caloptilia , in the global Caloptilia phylogeny and thus are very closely related (Nakadai & Kawakita ). We investigated the phenology (i.e.…”
Section: Introductionmentioning
confidence: 60%
“…Phylogenetic relationships of the 10 Caloptilia species, pruned from the global Caloptilia phylogeny (Nakadai & Kawakita ), and those of the nine Acer species, pruned from the global phylogeny of Japanese Acer (Nakadai et al . ), are shown. To facilitate interpretation, Caloptilia species with similar host plant use are placed close to each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the above mentioned ecological effects, there is evidence that foliar N concentration is evolutionarily conserved (Nakadai et al. , Oguro and Sakai , Werner et al. ), so that these exceptions to the general rule are unlikely to affect the generality of the reported phylogenetically conserved source–sink N gradient among species.…”
Section: Discussionmentioning
confidence: 99%